Stochastic simulations of storage and inventory systems - Bombała, Wojciech; Michna, Zbigniew (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2012)
This article aims to present the applications of Lévy processes for the stochastic modeling of storage resources. Two cases were considered. In the first one, the volume of supplies to the storehouse is described by a random process (Lévy process), while issuing the products is described by a deterministic and linear function. The second case is reversed: the delivery to the storehouse is described by a linear function (variable: time), while issuing the goods is described by a Lévy process. For both cases the form of the stock level process and examples of its trajectories, when the net supply is a Lévy process, are given. We investigated the following net supply processes: gamma process, α-stable Lévy process with α = 0.5, Cauchy process, Wiener process.
Mathematical Economics, 2012, Nr 8 (15), s. 17-28
Keywords: inventory system; storage system; stochastic processes; Lévy process; probability of an overflow